(untitled) (Revista de Ciências Agroveterinárias, 2020)
The objective of this study was to evaluate the floristic composition and phytosociological structure of a permanent preservation area in Alluvial Mixed Ombrophylous Forest in the Planalto Catarinense and to indicate potential tree species for the restoration of areas in similar sites. The study area is located in the municipality of Otacílio Costa, SC, on the banks of the Canoas River. For the floristic survey 24 plots of 10 m x 10 m were allocated in which all individuals with CAP ≥ 5 cm were measured, identified and quantified their phytosociological descriptors. The diversity was evaluate using the Shannon-Wiener diversity index (H’) and Pielou equability index (J). A total of 547 individuals belonging to 22 families were identified, distributed in 34 genera. Myrtaceae and Asteraceae as richer families. As for the regeneration guild, most species were classified as pioneers (45%), initial secondary and late secondary (26% each). Regarding the dispersion syndrome, the species were classified as zoochorous (71%), anemochorous (26%) and autochorous (3%). The Shannon-Wiener diversity index was 2.9 and the equability index was 0.78. The species with the highest values of importance, with potential for forest restoration, were Mimosa scabrella, Schinus terebinthifolius and Gymnanthes klotzschiana.